Behind closed doors! Homosocial desire and the academic boys club. Issue 1 (13th January 2014) - Fisher, Virginia; Kinsey, Sue
Abstract : Purpose: – The aim of this paper is to explore the nature and power of the academic boys club. In many organisations, the political significance of the boys club goes largely unremarked and unacknowledged. Yet, the way that male colleagues intimately relate to each other, sometimes called homosocial desire, is crucial to their success at gaining and retaining power at work. Design/methodology/approach: – Feminist, poststructuralist, ethnographic, qualitative, and longitudinal data were collected over a five-year period from male and female academics in a British university. Findings: – The boys club is still a powerful feature of British universities. Their apparent invisibility shrouds the manner in which they can and do promote and maintain male interests in a myriad of ways, including selection and promotion. These findings have resonances for all organisations. Research limitations/implications: – Researching the intimacies between male colleagues requires time-intensive field work and insider access to men interacting with each other. Practical implications: – Meaningful gender equality will not be achieved unless and until the more sophisticated forms of female exclusion are revealed and deconstructed. Originality/value: – This research makes an unusual and crucial contribution to the study of gender, men and masculinities by providing longitudinal, rich, detailed data, observing men at the closest of quarters and then analysed by a feminist and poststructuralist gaze.